Analisis Logit Model Pengguna Moda Transportasi ke Bandara Soekarno-Hatta - Talib, Nur Avifah Zahra; Nugroho, Aditya; Siahaan, Juaksa (Institut Transportasi dan Logistik Trisakti, 2025)
Soekarno-Hatta Airport is the busiest airport. There are so many means of transportation that connect to the airport, namely land transportation because air transportation and land transportation are interconnected and influence each other. Land transportation facilities on public transportation connecting to the airport are Airport Train, Private Vehicle, Damri Bus, Taxi, and Online Transportation. The purpose of this study is to analyze and determine the characteristics of mode selection, determine the choice model and determine the probability of mode selection at the research location at Soekarno-Hatta Airport by using a logit model to determine the probability of mode selection to Soekarno-Hatta Airport so that the research results show that the probability of airport trains is 94%, private vehicles by 86%, taxis by 0%, and Damri buses by 66% and online transportation by 74%. Then the results of the most selected research are airport trains with logit model calculations (-49,81046917 + 0,646064476 X 70 X1 + (-0,068540438) X 20 X2 + 0,12937047 X 47 X3) with variable costs, distance time.